ANALYSIS OF INCOME FROM CHOCOLATE BUSINESSES (CHOCOFFLES) IN THE CREATIVITY PROGRAM OF ENTREPRENEURSHIP STUDENTS - Sakinaturrizki Eka Putri; Baiq Nurul Fajriah; Yusril Hayadi; Illiyani Sholihatin; Muhamad Redi (Laboratorium Riset Ekonomi, 2023)
ANALYSIS OF INCOME FROM CHOCOLATE BUSINESSES (CHOCOFFLES) IN THE CREATIVITY PROGRAM OF ENTREPRENEURSHIP STUDENTS